Sosialisasi Peran Pelatih dan Tata Kelola Klub Bola Voli - sujarwo - jarwo (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2022)
The coach has a big role in the process of training and volleyball matches. This service has the aim of providing knowledge to coaches, volleyball administrators on how to foster volleyball clubs so that athletes become tough and achievers and become a big and trusted club by the community. The service method used is face-to-face socialization with participants on Wednesday, March 30, 2022, from 19.30 to 22.00 WIB. Located in one of the houses of the Bantul Morning Club management. There were 20 participants, consisting of 10 coaches, 5 administrators, and 5 referees from the Morning Volleyball Club. Evaluation of devotion using a t-test comparison between participants' knowledge and questions using the google form application. The target of service is the knowledge of the participants at a minimum score of 80. The results of the service using the t test, then the following results are obtained, the mean pretest result is 48, the posttest average result is 76, there is an increase in the average knowledge of coaches and club administrators, and there are 11 people who the target of service is above a score of 80. The conclusion in this service is that it is very necessary for coaches to understand and continue to learn about their role in developing volleyball, the management must continue to develop knowledge about volleyball club governance.